ANALISIS STRATEGI PENGEMBANGAN USAHA TAHU TEGUH PRIBADI DI BENGKULU TENGAH - Eska Prima Monique; Suswati Nasution (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
Small and medium enterprises (SMEs) which are now better known as micro and small enterprises play an important role in the growth of the Indonesian economy. The company carries out a SWOT analysis (Strength, Weakness, Oppurtunity, and Threat) in determining marketing strategies. The respondents in this study are tofu producers, suppliers, consumers, governments, competitors and marketing institutions of Tahu Teguh Pribadi. Where this analysis consists of 2 analysis variables, namely an analysis of internal factors consisting of strengths and weaknesses, and external analysis consisting of opportunities and threats. The IFAS (Internal Factor Analysis Summary) matrix shows that the strength and weakness factors have a total score of 3.01. The EFAS (External Factor Analysis Strategy) matrix shows that opportunity and threat factors have a total value of 3.16. Based on the Cartesian diagram shows that Usaha Tahu Teguh Pribadi is in the Growth quadrant where the quadrant is a very favorable situation. S-O strategy (Strenght-Opportunity) then obtained the factor that must be maintained to be able to take the opportunities that are: Improving product quality by utilizing technological developments to maintain consumer trust and forming associations / unions of business entrepreneurs to maintain bargaining positions against suppliers. The W-O strategy (Weakness-Opportunity) obtained results, namely: Increasing sales volume through product diversification by utilizing culinary policies and improving the quality of human resources through programs from the government. S-T strategy (Great Strenght) shows results: Improving quality and maintaining product continuity with good production management to improve competitiveness. And can improve marketing efficiency by establishing W-T (Weakness-Threat) Strategy partnership relationship, namely: Use simple SOPsfor effectiveness and efficiency. As well as increasing capital and promotion networks through product packaging and increasing human resources